The Role of the School Library in Supporting the Teaching and Learning Process and Student Literacy at SDN Sawojajar 1 - Anggraeni, Dela Resti; Riady, Yasir (Mitra Palupi, 2024)
Background: A school library is a library established by each school where the library has an important role in the student teaching and learning process. Purpose: This research aims to determine what efforts the Library at SDN Sawojajar 1 made to support the teaching and learning process and student literacy. Design and methods: This research uses a descriptive qualitative approach. The data collection techniques used were observation, interviews, and documentation. Results: The results of the research show that the efforts made by the SDN Sawojajar 1 Library, which plays a role in supporting the teaching and learning process and literacy, are by providing various kinds of collections, implementing the Steel Corner program, implementing the literacy movement (GLS) program, and making library visits mandatory. The policy of providing a collection of textbooks, applicable books, and references helps meet students' needs in understanding the school curriculum. It stimulates interest in reading outside the context of formal learning. The Reading Corner Program provides opportunities for students to read books according to their interests. In contrast, the Literacy Movement (GLS) provides a holistic approach by integrating audio-visual media to improve student literacy. With the various efforts made by the library, it is hoped that it can become a dynamic and effective learning center in supporting the teaching and learning process and increasing student literacy at SDN Sawojajar 1.